New Product Acceptance: A Study of Organic Milk - Banga, Gagandeep; Kumar , Babita; Bhatt, weeraj Kumar (Gyan Management Journal, 2009)
The consumer is quite concerned about health issues and is taking great interest in food matters. Besides, I.he green movement supported by media coverage has been creating increasing urge for natural foods. The controversies, often reported in the media, such as genetically modified food mad cow disease, dioxin in animal feed and various .1candals of selling contaminated processed food etc. have also been creating widespread scare amongst consumers. These concerns are leading to introduction and populariza_tion of organic foods and dairy sector is no exception. The present study was undertaken to understand the awarene :s, perception and altitude of potential consumers towards organic milk. The study revealed th.at the consumers perceive organic milk as nutritious and healthy product and have a positive attitude towards it and was willing to pay 25 percent more price far organic milk as compared to conventional milk.